2005
DOI: 10.1111/j.1365-2591.2005.00945.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cryogenic treatment on nickel‐titanium endodontic instruments

Abstract: Aim-To investigate the effects of cryogenic treatment on nickel-titanium endodontic instruments. The null hypothesis was that cryogenic treatment would result in no changes in composition, microhardness or cutting efficiency of nickel-titanium instruments.Methodology-Microhardness was measured on 30 nickel-titanium K-files (ISO size 25) using a Vicker's indenter. Elemental composition was measured on two instruments using X-ray spectroscopy. A nickel-titanium bulk specimen was analysed for crystalline phase co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 29 publications
2
44
1
2
Order By: Relevance
“…17,18) Cryo-treatment immerses the samples in a cold medium (such as liquid nitrogen) according to a certain processing curve until achieving a certain temperature. The material's performance will be improved by inducing microstructural changes and stress redistribution.…”
Section: Introductionmentioning
confidence: 99%
“…17,18) Cryo-treatment immerses the samples in a cold medium (such as liquid nitrogen) according to a certain processing curve until achieving a certain temperature. The material's performance will be improved by inducing microstructural changes and stress redistribution.…”
Section: Introductionmentioning
confidence: 99%
“…61 Finally, surface hardening can be achieved through cryogenic treatment. 62 The samples tested showed increased microhardness but no detectable change in crystalline phase composition or elemental composition. This was also confirmed by another study that concluded that deep dry cryogenic treatment "increases the cutting efficiency significantly but not the wear resistance."…”
Section: Surface Treatment Of Niti Alloysmentioning
confidence: 89%
“…Anderson et al in 2007 showed that electropolished instruments performed significantly better than non-electropolished instruments in both the cyclic fatigue testing and static torsional loading, which is likely to be caused by a reduction in surface irregularities that serve as points of stress concentration and crack initiation in nickel titanium. 21 Kim et al 2005 22 studied the effect of cryogenic treatment on nickel-titanium endodontic instruments.30 size 25 nickeltitanium K-files (NTO2525; Dentsply-Tulsa Dental) were embedded in epoxy resin (811-563-103 and 811-563-104; Leco, St Joseph, MI, USA) mixed according to the manufacturer's instructions. 15 control instruments and 15 cryogenically treated instruments were used.…”
Section: Discussionmentioning
confidence: 99%